SOSIALISASI PROGRAM STICOM DAN PRAKTIK BUDIKDAMBER DI KAMPUNG MAKBUSUM, DISTRIK MAYAMUK, KABUPATEN SORONG: Sosialisasi Program Sticom Dan Praktik Budikdamber Di Kampung Makbusum, Distrik Mayamuk, Kabupaten Sorong - Ernawati Ernawati; Hendra Poltak; Rezza Ruzuqi; Agung Setia Abadi; Asthervina Widyastami Puspitasari; Intanurfemi Bacandra Hismayasari; kadarusman kadarusman; Boby W Ziliwu; Bagas Prakoso (Politeknik Kelautan dan Perikanan Sorong, 2022)
STICOM (Smart Tilapia Community) is a program initiated by the study program. Sorong Marine and Fisheries Polytechnic Fisheries Cultivation Techniques collaboration with the Majaran Fish Seed Center. This activity expected to increase public awareness about the use of land or narrow areas to cultivate fish such as vegetables that are effective in buckets. That this will also increase the income of the residents of the Mayamuk district. Then the activity was carried out using the STICOM socialization method and the practice of making BUDIKDAMBER (fish in buckets). The socialization activity invited the residents of the Mayamuk district. After that a satisfaction survey was carried out. The results obtained are that the Mayamuk community is satisfied with the activities that have been carried out by the team and hopes that these activities will be repeated to evaluate activities.